Protagonistas de narrativas juvenis contemporâneas: de mãos dadas com o jovem leitor - SANTOS, Dayse Rodrigues dos (2020)
The reflection on the representation of identity in the feminine authored youth literature raises questions about the elements that constitute it, including the situations that may bother the reader. The books that make up the corpus of this research are authored by the award-winning writer Heloisa Prieto, Lenora (2008) and Ian – a música das esferas (2015), published by Rocco - Young Readers, in the series “To Die in Fear”. In these narratives, she thematizes the supernatural power of music, its influence, and the bond that unites the lives of the two homonymous characters, as well as that of the protagonist of the second book. The choice of these books is justified because they constitute a series not yet analyzed together, both shadowy youth novels of female authorship, in which there is an evident search for identity. In this sense, the debate on the concepts of Identity and youth will be held mainly by theoretical framework of Contardo Calligaris (2000), Zygmunt Bauman (2005) and Stuart Hall (2014). The theoretical references on youth literature and literature in a broad sense are centered on João L. Ceccantini (2000) and Maria Zaira Turchi (2002) and Antonio Candido (2011), among others that may endorse this research. Among the final results, there is a dialogue with the potential young reader as it addresses identity and overcoming in a respectful way to the target audience's psyche